Gender interaction in traditional games: A socio-cultural study and character education implications - Dwi Prasetyo (Universitas Airlangga, 2026)
Traditional games in East Java hold significant cultural value, shaping social interaction and identity among children and adolescents. However, gender interaction patterns within these games often mirror societal norms that limit roles for boys and girls. Physical games such as Egrang and Bentengan are typically dominated by boys, while girls tend to engage in collaborative and strategic games like Gobak Sodor. This dynamic raises important questions about how play influences the internalization of gender roles. This study explores gender interaction patterns in East Java’s traditional games and the socio-cultural factors behind them. Using a qualitative phenomenological approach, the research focuses on the lived experiences of children (ages 11–12) and adolescents (ages 18–19). Data were gathered through participant observation and in-depth interviews to capture their interpretations of gender roles during play. Findings reveal strong gender segregation in physical games, yet strategic games offer spaces for collaboration. Interestingly, adolescents increasingly challenge stereotypes by choosing games based on personal interest rather than cultural expectations. These insights suggest that traditional games can foster values of equality, teamwork, and inclusivity. Beyond cultural preservation, they serve as platforms for character education, promoting gender equity and social cohesion.